66.7k views
1 vote
Given f(x)=5x^2-2x and 3x^2+x-4. What is (f+g)(x)?

Given f(x)=5x^2-2x and 3x^2+x-4. What is (f+g)(x)?-example-1

2 Answers

3 votes

Answer:(f + g)(x) = f (x) + g(x)

= [3x + 2] + [4 – 5x]

= 3x + 2 + 4 – 5x

= 3x – 5x + 2 + 4

= –2x + 6

(f – g)(x) = f (x) – g(x)

= [3x + 2] – [4 – 5x]

= 3x + 2 – 4 + 5x

= 3x + 5x + 2 – 4

= 8x – 2

(f × g)(x) = [f (x)][g(x)]

= (3x + 2)(4 – 5x)

= 12x + 8 – 15x2 – 10x

= –15x2 + 2x + 8

\left(\small{\dfrac{f}{g}}\right)(x) = \small{\dfrac{f(x)}{g(x)}}(

g

f

)(x)=

g(x)

f(x)

= \small{\dfrac{3x+2}{4-5x}}=

4−5x

3x+2

Explanation:

To find the answers, all I have to do is apply the operations (plus, minus, times, and divide) that they tell me to, in the order that they tell me to.

User Plaureano
by
5.1k points
5 votes

Answer:

The correct option is:
8x^2-x-4

Explanation:


f(x)= 5x^2-2x\\ \\ g(x)= 3x^2+x-4

So,
(f+g)(x)


= f(x)+g(x)\\ \\ =(5x^2-2x)+(3x^2+x-4)\\ \\ =(5x^2+3x^2)+(-2x+x)-4\\ \\ =8x^2-x-4

User Kalinka
by
4.9k points